Keperluan Latihan Pegawai-Pegawai Barisan Hadapan RISDA(Training Needs of RISDA's Frontline Workers) - Ismail, Maimunah; Ahmad, Asma (1985)
A study was conducted among 194 RISDA'sfrontline workers throughout Peninsular Malaysia. The aim of the study was to identify front line workers' training needs in technical and non-technical areas. The findings of the study should serve as a useful guide in curriculum development for inservice training of RISDA 's front line workers. The study indicated that the front line workers need training in the areas related to the modernization programme specifically in diversifying income sources for the rubber smallholders. The areas identified are the rearing of sheep, cattle and buffaloes (76 per cent), fresh-water fish rearing (73.65 per cent), agricultural economics (73.4 per cent) and poultry rearing (73.28 per cent). The officers were also found to have low job-competencies in these areas probably because the areas are comparatively new within the. whole range of rubber smallholders development programmes.